2017
DOI: 10.1186/s13065-017-0257-5
|View full text |Cite
|
Sign up to set email alerts
|

Non-destructive determination of ethanol levels in fermented alcoholic beverages using Fourier transform mid-infrared spectroscopy

Abstract: BackgroundTraditional fermented alcoholic beverages are indigenous to a particular area and are prepared by the local people using an age-old techniques and locally available raw materials. The main objective of this work was the direct determination of ethanol in traditional fermented alcoholic beverages using mid infrared spectroscopy with partial least squares regression, verifying the robustness of the calibration models and to assess the quality of beverages.ResultsThe level of ethanol determination in Et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 49 publications
1
14
0
6
Order By: Relevance
“…The direct determination of ethanol in traditional fermented alcoholic beverages using mid infrared spectroscopy with partial least squares regression (MIR-PLS) has also been reported [24]. The MIR-PLS predicted values were found to be in excellent agreement with gas chromatographic measurements.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The direct determination of ethanol in traditional fermented alcoholic beverages using mid infrared spectroscopy with partial least squares regression (MIR-PLS) has also been reported [24]. The MIR-PLS predicted values were found to be in excellent agreement with gas chromatographic measurements.…”
Section: Introductionmentioning
confidence: 91%
“…However, it should be noted that the present procedure is probably not usable for regulatory purposes (e.g. controlling labelling) [24].…”
Section: Introductionmentioning
confidence: 95%
“…These are mineral contents in tea (Gebretsadik and Chandravanshi, 2010), coffee (Ashu and Chandravanshi, 2011), mineral waters (Seda et al, 2013), wines (Woldemariam and Chandravanshi, 2011), ouzo (Bekele and Chandravanshi, 2012), traditional fermented alcoholic beverages (Debebe et al, 2017a). Phenolic contents (Debebe et al, 2016) and level of alcohol in fermented (Debebe et al, 2017b) and distilled (Debebe et al, 2017c) alcoholic beverages have also been reported. However, to the best of our knowledge, no systematic study on the levels of trace heavy metals and physicochemical parameters in Ethiopian honey has been made.…”
Section: Introductionmentioning
confidence: 96%
“…Инфракрасный спектр продукта позволяет выявлять большое количество соединений, образующихся в ходе технологического процесса его получения, что позволяет осуществлять текущий контроль путем систематической обработки спектров во времени [4]. Для оценки динамики отслеживаемого процесса важно знать количественное соотношение искомых веществ, что устанавливается по интенсивности полос поглощения, отражающих присутствие соединений с данными функциональными группами в анализируемом продукте, и подготовленным градуировочным характеристикам [5].…”
Section: Introductionunclassified
“…Вино -достаточно сложный по составу продукт, различные компоненты которого имеют одинаковые функциональные группы, нахождение концентрации единственного вещества по «общей» группе возможно лишь при условии, что определяемое вещество находится в известном, постоянном количественном соотношении с веществами, имеющими эту же группу, чтобы обеспечить выделение характеристической полосы поглощения для искомого вещества и установление градуировочной характеристики по ней. Так, гидроксильную группу содержат вода, спирты, органические кислоты, фенольные вещества и др., поэтому полоса поглощения гидроксильной группы имеет недостаточную резкость и специфичность, чтобы использовать ее для количественного анализа [5]. Решение проблемы состоит в использовании для градуировки в качестве образца сравнения испытуемого продукта, что обеспечит нужное соотношение компонентов и исключит необходимость приготовления большого количества модельных растворов [9].…”
Section: Introductionunclassified